MERLINO. Virtual Reality for Stimulation of Neuro-cognitive Processes - Mario Bisson; Shanti Andreana Alberti di Catenajo; Stefania Palmieri (Agathón)
This research investigates studies on multi-sensory environments (MSEs) and, comparing existing solutions on the market, offers an integrated product-service, designed to contain costs, from an industrial manufacturing perspective, with a high level of flexibility, aimed at children with intellectual and motor disabilities. Based on the studies developed by the LudoMi team, a project awarded at Polisocial Award 2017, as acknowledgment on research with a high social impact relevant for the scientific community. We report the case study of Merlino: research project, in progress, with the Design Department of the Polytechnic of Milan, which aims to increase the development of cognitive faculties and motor skills, promoting learning and improvement of communication and relational skills.